Data Protection for Sexual Violence Victims in the Court Case Tracking Information System: English - Mansyah, Muh Sutri; Kaswandi; Hasirudin Hasri; Hayun; Rasmala Dewi; Darojatun Andara; Edy Nurcahyo (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
The Case Tracking Information System is a system established by the Supreme Court which functions to track a case. However, in reality, it has been found that sensitive information regarding victims of sexual violence, such as names that should be kept confidential, is disclosed. The purpose of this research is to examine and evaluate the case tracking information system regarding data on child victims and to develop an ideal model for protecting the data of victims of sexual violence within the case tracking information system. The research method used is normative juridical research with a case approach, statutory regulations, and conceptual approaches. The research findings indicate that five laws (the Witness and Victim Protection Law, the Sexual Violence Crime Law, the Personal Data Protection Law, the Juvenile Justice System Law, and the Child Protection Law) regulate the confidentiality of victims to prioritize the best interests of children as the nation’s future generation. However, in reality, it has been found that some courts, such as the Baubau District Court, display information such as the victim’s name, while the Pasarwajo District Court in SIPP only displays the victim’s data in the form of a pseudonym, namely a child witness.